Developmental competence of transported in-vitro matured macaque oocytes - Abdullah, Ramli; Ng, S.C.; Chen, N.; Liow, S.L.; Tong, G.Q.; Embong, W.K.W.; Yip, W.Y.; Tan, L.G. (2006)
This study examines in-vitro maturation (IVM) in a non-human primate model, Macaca fascicularis. The animals had hormonal injections and laparoscopic oocyte retrieval (OR)) at 12- and 24- h after human chorionic gonadotrophin (HCG). The immature oocytes were placed in tightly capped tubes containing pre-equilibrated IVM medium and transported for 5 h in a dry portable 37°C incubator without CO 2 supplement. Meiotic spindle was observed at 36-38- h post-HCG by polarized microscopy in 72 and 84.5% of mature oocytes collected at 12- and 24- h post-HCG ooeyte retrieval intervals respectively. However, abnormal spindle formations were detected in some IVM oocytes by confocal microscopy. The IVM oocytes were also randomly selected for (i) intracytoplasmic injection with frozen-thawed epididymal M. fascicularis spermatozoa and (ii) nuclear transfer (NT) with fresh M. fascicularis cumulus cells. Embryonic development of sperm-injected embryos was not affected by the 12- and 24- h post-HCG oocyte retrieval intervals (22.5 versus 27.9% respectively). However, embryonic development of NT embryos was significantly affected by the 12- h post-HCG oocyte retrieval interval (4.5 versus 31.7% respectively; P < 0.01). In conclusion, IVM of monkey oocytes in a dry portable incubator for 5 h did not affect the maturation rate. However, the ability of primate oocytes to develop after somatic cell nuclear transfer was affected by oocyte retrieval time post-HCG.